Eating identities : reading food in asian american literature (2008)
Allow me to begin with two stories. During the Chinese Cultural Revolution (1966–1976), hunger dominated my life in Baoding, Hebei Province, China, as it did millions of others. Only a small elite had access to protein, and their currency was power. Unlike abject starvation, the hunger I experienced permitted fantasies, such as meats, sweets, and fancy pastries. My family often sat at the dinner table after a meal of corn bread and boiled cabbage to continue eating imaginary delicacies. We would share in great detail the most delicious dishes we had ever eaten—their rare ingredients, their elaborate cooking, their distinctive tastes, and their spectacu- lar presentations. The hungrier we were, the more extravagant our descriptions. On one of these occasions, when I began talking about my favorite Southern dessert, tang yuan, my father told the following story: when the British went to China in the late 1600s, one of the things about China that puzzled the British was tang yuan. “They liked the sticky rice ball very much,” he said. “It’s chewy and creamy at the same time. A burst of rich, fragrant sweetness goes off in your mouth like a bomb. The British had never tasted anything like it. That’s why it really bothered them that they couldn’t figure out how the Chinese put the sweet filling inside seamless balls. They took a few samples of tang yuan to their lab and dissected them. What they found in the center was a dark mass. It didn’t take them long to figure out that the dark substance consisted of brown sugar, lard, and sesame seeds. Since it congeals when cold and a mass is more difficult to insert into a ball than liquid, the Chinese must have melted the substance first. After repeated experiments, the English scientists finally came to the conclusion that the Chinese injected into sticky rice balls a sugar-lard- sesame seed syrup with a large hypodermic needle.” My father laughed and slapped his thigh at this point. “Of course, they proudly sent their finding to Queen Victoria.”